Target actionability review to evaluate CDK4/6 as a therapeutic target in paediatric solid and brain tumours - Schubert, Nil A.; Chen, Celine Y.; Rodríguez, Ana; Koster, Jan; Dowless, Michele; Pfister, Stefan; Shields, David J.; Stancato, Louis F.; Vassal, Gilles; Caron, Hubert N.; van den Boogaard, Marlinde L.; Henssen, Anton George; et al. (European journal of cancer, 2022)
Background - Childhood cancer is still a leading cause of death around the world. To improve outcomes, there is an urgent need for tailored treatment. The systematic evaluation of existing preclinical data can provide an overview of what is known and identify gaps in the current knowledge. Here, we applied the target actionability review (TAR) methodology to assess the strength and weaknesses of available scientific literature on CDK4/6 as a therapeutic target in paediatric solid and brain tumours by structured critical appraisal. - Methods - Using relevant search terms in PubMed, a list of original publications investigating CDK4/6 in paediatric solid tumour types was identified based on relevancy criteria. Each publication was annotated for the tumour type and categorised into separate proof-of-concept (PoC) data modules. Based on rubrics, quality and experimental outcomes were scored independently by two reviewers. A third reviewer evaluated and adjudicated score discrepancies. Scores for each PoC module were averaged for each tumour type and visualised in a heatmap matrix in the publicly available R2 data portal. - Results and conclusions - This CDK4/6 TAR, generated by analysis of 151 data entries from 71 publications, showed frequent genomic aberrations of CDK4/6 in rhabdomyosarcoma, osteosarcoma, high-grade glioma, medulloblastoma, and neuroblastoma. However, a clear correlation between CDK4/6 aberrations and compound efficacy is not coming forth from the literature. Our analysis indicates that several paediatric indications would need (further) preclinical evaluation to allow for better recommendations, especially regarding the dependence of tumours on CDK4/6, predictive biomarkers, resistance mechanisms, and combination strategies. Nevertheless, our TAR heatmap provides support for the relevance of CDK4/6 inhibition in Ewing sarcoma, medulloblastoma, malignant peripheral nerve sheath tumour and to a lesser extent neuroblastoma, rhabdomyosarcoma, rhabdoid tumour and high-grade glioma. The interactive heatmap is accessible through R2 [r2platform.com/TAR/CDK4_6].
Gesehen am 25.09.2022